Record of longhorn beetle (Aeolesthes holosericea) on mango in the Punjab - SINGH, SANDEEP; SREEDEVI, KOLLA (The Indian Journal of Agricultural Sciences, 2019)
Roving and fixed plot surveys were conducted in mango growing areas of the Indian Punjab to record the emerging insect pests. During these surveys, longhorn beetle, Aeolesthes holosericea (Fabricius, 1787) (Coleoptera: Cerambycidae) was observed for the first time on mango in the Indian Punjab, infesting stems of 25 to 40 years old trees at Government Garden and Fruit Nursery, Bhunga, district Hoshiarpur during 2017. The stem borer was active from February to November, with peak activity during August to October. Grubs were observed in the stem and below the bark. The number of grubs from a single tree ranged from 2.1 to 30.3, while number of beetles per tree ranged from 5.7 to 32.3. About 40.3% trees in the orchard were found to be infested by the borer. Continuous monitoring and integrated management of this beetle needs attention so that the borer may not spread to other fruit crops and forest trees in Punjab. This study concludes that A. holoserica might be a new emerging stem borer pest of mango trees in the Indian Punjab.